2007
DOI: 10.1128/mcb.01153-06
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasia Driven by Mutant c-KIT Is Mediated by Intracellular, Not Plasma Membrane, Receptor Signaling

Abstract: Activating mutations in c-KIT are associated with gastrointestinal stromal tumors, mastocytosis, and acute myeloid leukemia. In attempting to establish a murine model of human KIT D816V (hKIT D816V )-mediated leukemia, we uncovered an unexpected relationship between cellular transformation and intracellular trafficking. We found that transport of hKIT D816V protein was blocked at the endoplasmic reticulum in a species-specific fashion. We exploited these species-specific trafficking differences and a set of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 40 publications
13
121
1
Order By: Relevance
“…20 Similar intracellular retention and corroborating STAT5 activation was also observed for oncogenic KIT mutants. 47 Here, we show the same localization-dependent skewed signaling behavior for F/PDGFRa. Together, all these data show that increased intracellular localization shifts the signaling capacities of the PDGFR/KIT/ Flt3 family of receptors in a variety of cell types.…”
Section: Discussionsupporting
confidence: 55%
“…20 Similar intracellular retention and corroborating STAT5 activation was also observed for oncogenic KIT mutants. 47 Here, we show the same localization-dependent skewed signaling behavior for F/PDGFRa. Together, all these data show that increased intracellular localization shifts the signaling capacities of the PDGFR/KIT/ Flt3 family of receptors in a variety of cell types.…”
Section: Discussionsupporting
confidence: 55%
“…Although cell surface expression of the KIT D816V receptor is reduced and its localization shifted to the Golgi apparatus, it has been demonstrated that KIT D816V activates the major signaling pathways that are also induced by the ligand-dependent wild-type receptor. 25 Implication of the D816V mutation in the pathogenesis of myeloproliferative disease demonstrates a critical role of KIT D816V transduced signals in the development of myeloid cells. 26,27 Although extrapolations regarding the physiological mechanisms of Kit signaling during myeloid cell differentiation must be made with caution, it is thus reasonable that similar signaling events are activated by the mutant KIT D816V receptor and valuable insights can be provided by such a model.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor consists of the murine extracellular and transmembrane domains and the human intracellular domain (Supplementary Figure 1A) and shows fully transforming potential in murine cells. 25 We linked the KIT cDNA to a green fluorescent protein (GFP) coding sequence from copepod Pontellina plumata by a viral 2A-sequence 28 to generate the GFP-2A-KIT D818V fusion protein, hereafter called KIT D816V . During translation the 2A-peptide mediates separation of GFP and KIT, allowing reliable tracking with minimal alteration of the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…For immunostaining, cells were directly fixed in 2% paraformaldehyde, permeabilized with ethanol, and stained with primary antibodies for 12 hours followed by labeled secondary antibodies. 40,41 The primary antibodies used were as follows: anti-Fms rat IgG (clone 3-4A4-E4; Abcam, Cambridge, MA), anti-GM130 mouse IgG (Transduction Laboratories), anti-CD8 rabbit IgG (H-160; Santa Cruz Biotechnology), and rabbit IgG specific for Hck phosphorylated at Tyr411 (Santa Cruz Biotechnology). The labeled secondary antibodies used were as follows: anti-rat IgG-AlexaFluo488, anti-mouse IgG-AlexaFluo568, and anti-rabbit IgG-AlexaFluo488 (Molecular Probes, Eugene, OR).…”
mentioning
confidence: 99%